Using weighting functions to detect multiple outliers : laporan teknik - Mohd. Nor Mohamad; Robiah Adnan; Halim Setan, 1957-; Universiti Teknologi Malaysia. Fakulti Sains. Jabatan Matematik (Skudai : Universiti Teknologi Malaysia, 1999)
36